Costa Rica : Fiscal Transparency Assessment. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses pilot fiscal transparency assessment for Costa Rica. The assessment confirmed that Costa Rica has various excellent and sophisticated fiscal transparency practices. Those include: (1) institutional coverage with annual consolidated budgetary information for the entire public sector and monthly information for the Executive Branch; (2) information produced regarding tax expenditures; (3) an independent Office of the Comptroller General of the Republic that audits budget balances by May of the following year; and (4) a medium-term budgetary framework and budgetary projections with forecasts of key macroeconomic variables and the assumptions on which they are based. However, weaknesses do persist in some areas.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet